ANALISIS MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM MENINGKATAN MUTU LULUSAN DI SMAN 2 HALONG KABUPATEN BALANGAN - Miranti Miranti (CV. ADIBA AISHA AMIRA, 2023)
This study concerns education financing management and graduate quality, which aims to analyze the education financing management process which has an impact on improving the quality of graduates at SMAN 2 Halong. This research uses a qualitative approach with descriptive methods. The data sources in this study are primary data and secondary data with the data collection techniques being observation, interviews, and documentation. The informants in this interview were the principal, treasurer, and teacher. Data analysis was carried out by qualitative analysis which included data reduction, data presentation, and drawing conclusions. Meanwhile, to check the validity of the data, researchers used triangulation and source triangulation techniques. The results of this study indicate that SMAN 2 Halong's education financing management includes three ways, namely; 1) Planning, where school-related activities have been prepared in the School Activity and Budget Plan (RKAS) which is prepared by the school every year at the beginning of the school year. 2) Implementation, where for the implementation of financing there is receipt of funding such as School Operational Assistance (BOS) funds, school business units, activity money, and community donations. Expenditure, such as teacher and staff salaries, administrative needs, teaching and learning support, procurement and maintenance of infrastructure, activities for alumni and parents, as well as subscriptions to services and resources. 3) Evaluation, this is carried out by SMAN 2 Halong twice every year, in the middle and at the end of the school year by holding meetings with related parties. The results of the evaluation can be used as a reference by the school to make a decision. The educational financing management process at SMAN 2 Halong has an impact on improving the quality of graduates. This can be seen from the various types of activities carried out at SMAN 2 Halong with the aim of developing student character by applying religious culture at school, and improving student skills referring to 4C competencies, both intra- curricular and extra-curricular activities. In addition, there is the satisfaction of parents of students with graduates of SMAN 2 Halong who have personalities in accordance with the school's vision and mission.